Implementation of Agroforestry System of Bakubakulu Village Communities - Andi Sahri Alam; Rafiuddin; Imran Rachman; Hendra Pribadi; Erniwati; Hamzari (Jurnal Penelitian Pendidikan IPA, 2024)
The community in Bakubakulu Village, Palolo District, Sigi Regency, is one of the communities that is developing an agroforestry system. This research aims to determine the agroforestry patterns used on community land in Bakubakulu Village. This research was carried out for 3 months, from October to December 2022. Respondents were taken in this research using the Purposive Sampling technique, namely deliberate (not random) sampling of respondents according to the criteria. Data were analyzed using descriptive methods. Respondents' research results on agroforestry patterns according to the time dimension are Intermittent on sloping land and Coincident on flat land. According to the spatial aspect, the pattern respondents use is Regular Temporary on flat land and Random Permanent on sloping land. The types of plants most commonly planted by the community are candlenuts, sugar palms, cocoa, cloves, and coconuts. The Regular Temporary Pattern is the pattern most frequently applied by respondents